Developmental Programming: Impact of Gestational Steroid and Metabolic Milieus on Adiposity and Insulin Sensitivity in Prenatal Testosterone-Treated Female Sheep - Cardoso, Rodolfo C. (Endocrinology, 2016)
Prenatally testosterone (T)-treated sheep present metabolic disruptions similar to those seen in women with polycystic ovary syndrome. These females exhibit an increased ratio of small to large adipocytes, which may be the earliest event in the development of adult insulin resistance. Additionally, our longitudinal studies suggest the existence of a period of compensatory adaptation during development. This study tested whether 1) in utero cotreatment of prenatally T-treated sheep with androgen antagonist (flutamide) or insulin sensitizer (rosiglitazone) prevents juvenile insulin resistance and adult changes in adipocyte size; and 2) visceral adiposity and insulin sensitivity are both unaltered during early adulthood, confirming the predicted developmental trajectory in this animal model. Insulin sensitivity was tested during juvenile development and adipose tissue distribution, adipocyte size, and concentrations of adipokines were determined during early adulthood. Prenatal T-treated females manifested juvenile insulin resistance, which was prevented by prenatal rosiglitazone cotreatment. Neither visceral adiposity nor insulin sensitivity differed between groups during early adulthood. Prenatal T-treated sheep presented an increase in the relative proportion of small adipocytes, which was not substantially prevented by either prenatal intervention. A large effect size was observed for increased leptin concentrations in prenatal T-treated sheep compared with controls, which was prevented by prenatal rosiglitazone. In conclusion, gestational alterations in insulin-glucose homeostasis likely play a role in programming insulin resistance, but not adipocyte size distribution, in prenatal T-treated sheep. Furthermore, these results support the notion that a period of compensatory adaptation of the metabolic system to prenatal T exposure occurs between puberty and adulthood.